2017
DOI: 10.3390/su9020175
|View full text |Cite
|
Sign up to set email alerts
|

Household Livelihood Strategy Choices, Impact Factors, and Environmental Consequences in Miyun Reservoir Watershed, China

Abstract: Abstract:Household livelihood strategies are embedded in the natural and socioeconomic contexts in which people live. Analyzing the factors that influence household livelihood choice and defining their consequences can be beneficial for informing rural household policies. In turn, this has great significance for fostering sustainable livelihood strategies. We grouped household livelihood strategies based on the income distribution of 756 households and analyzed their influencing factors and possible livelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 35 publications
5
38
0
2
Order By: Relevance
“…Similar to other studies [48][49][50], our study also indicated that the rural households with a high percentage of healthy adults favor the adoption of mixed livelihood strategy. The healthier adults there are, the more likely they have enough manpower to engage new livelihood activities.…”
Section: Key Influencing Factors On Livelihood Strategy Choice In Earsupporting
confidence: 90%
“…Similar to other studies [48][49][50], our study also indicated that the rural households with a high percentage of healthy adults favor the adoption of mixed livelihood strategy. The healthier adults there are, the more likely they have enough manpower to engage new livelihood activities.…”
Section: Key Influencing Factors On Livelihood Strategy Choice In Earsupporting
confidence: 90%
“…In past livelihood-related studies, communities and rural households were all categorized into different types; for example, rural households were categorized into three types, i.e., market-oriented quantized value, part-time quantized value, and non-farming household according to the livelihoods of the rural households [40]; project household and non-project household according to the types of the project [62]; and semi-mountain settlement, river valley settlement, high-mountain settlement, and resettlement area according to the geographical locations [38]; farm households and off-farm households according to the types of the livelihoods [41]. There are three main methods used to classify tourism communities: (1) the communities are categorized into inner scenic attraction regions and peripheral or adjacent regions according to geospatial features [31,[69][70][71]; (2) the communities are categorized according to administrative divisions [72,73]; and (3) the communities are categorized according to livelihoods [74].…”
Section: Community Type Classificationmentioning
confidence: 99%
“…In recent years, some scholars have noted that in the framework of sustainable livelihood, evaluation with the combination of income and livelihood assets in studying community livelihoods is more comprehensive than that with only livelihood assets or income [35]. Investigations on community livelihoods using the sustainable livelihood method with the combination of income and livelihood assets have been extensively conducted in rural economics and management and other fields [36][37][38][39][40][41]; however, livelihood assets have been used as a factor affecting income in few tourism studies. For example, from the perspective of livelihood assets, Truong et al found that the lack of livelihood capital is an important reason for limited tourism income in residents using the sustainable livelihood approach [42].…”
Section: Introductionmentioning
confidence: 99%
“…Several key factors (including geographical location, the natural environment, household structure, labor quality, and ecological policies) could affect a household's livelihood capital, livelihood risk, and vulnerability, and thus constantly influenced the relationship between households and their dependency on the ecosystem [34][35][36][37][38][39]42] (Table 4). Among the four types of households, the formation of an H-H household was characterized first by a large area of land suitable for cultivation (Table 2) and a strong reliance on food crops or economic crops as the main livelihood [51,63].…”
Section: Impact Factors Of Household Welfare-ecosystem Dependency Relmentioning
confidence: 99%
“…The dependence of household welfare on the ecosystem is mainly affected by its geographical location [34], the level of natural capital [35], number of family members [24,36], the labor quality, and ecological policies [37][38][39].We selected eight independent variables from these five aspects, which were: distance from Beijing, cultivated area, household size, the average age of household laborers, the average education level of laborers, skills, training, and the amount paid from ecological compensation funds. Statistically significant differences were analyzed using one-way ANOVA with the software SPSS v.19.…”
Section: Factors Influencing the Relationships Between The Ecosystem mentioning
confidence: 99%